1980
DOI: 10.1055/s-0038-1650010
|View full text |Cite
|
Sign up to set email alerts
|

Marathon Run III: Effects on Coagulation, Fibrinolysis, Platelet Aggregation and Serum Cortisol Levels

Abstract: SummaryBlood coagulation, fibrinolysis, platelet count-aggregation and Cortisol were assessed in 35 Finnish amateur runners aged 27 to 56 years (mean 40) and three aged 65, 67, and 82 who had run a non-competitive Marathon in 1975, 1976 and 1977 over the classical itinerary. After the run, in all 3 years, APTT showed shortening (p < 0.001); prothrombin time and plasma fibrinogen were not significantly altered; euglobulin lysis time was shorter (p < 0.001) and FDP increased (p < 0.001); PSPT became pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 2 publications
(3 reference statements)
2
12
0
Order By: Relevance
“…12,13 Rock and colleagues 15 reported that 24 hours after participation in a marathon, platelet aggregation in response to epinephrine, ADP, and collagen was decreased, indicating activation during the period of exercise. Similarly, Knudsen and coworkers 14 reported decreases in ADP-induced platelet "aggregability" and decreased serotonin release induced by ADP and collagen after long-distance running, consistent with exhaustion of platelet aggregation capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Rock and colleagues 15 reported that 24 hours after participation in a marathon, platelet aggregation in response to epinephrine, ADP, and collagen was decreased, indicating activation during the period of exercise. Similarly, Knudsen and coworkers 14 reported decreases in ADP-induced platelet "aggregability" and decreased serotonin release induced by ADP and collagen after long-distance running, consistent with exhaustion of platelet aggregation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…2,[5][6][7][8][9] In the majority of studies, platelet counts were elevated and there was evidence of platelet activation following prolonged exertion. [10][11][12][13][14][15] Many of the investigations focusing on platelets measured in vitro platelet aggregation or soluble factors correlated with platelet activation; such studies are labor-intensive and require highly trained personnel and specialized equipment, limiting their availability in many settings, and provide only indirect evidence of in vivo platelet activation.…”
mentioning
confidence: 99%
“…The activation of these systems is less pronounced in athletes than untrained runners. 38 In healthy subjects, the activation of the cascades should work to maintain the balance between the two systems, 16 38 47 but if the activation of these systems is not in balance, a predisposition to thrombus formation may be the result. In a group of patients followed up for one hour after exercise, Hegde et al 17 found that, although t-PA antigen level declined gradually over the hour, activated partial thromboplastin time remained shortened, suggesting continued activation of coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…18 The cascade also has its own regulatory proteins that inhibit coagulation at various stages, such as antithrombin III and protein C. These inhibitors of coagulation are also affected by exercise, although the results of studies looking at this are not so conclusive. Antithrombin III has been shown to fall in one study, 38 although little change was seen in others. 13 14 Ferguson et al 12 describe a rise in absolute antithrombin III concentration, but a fall in concentration once corrections were made for plasma volume, suggesting consumption of the factors.…”
Section: Findings Coagulationmentioning
confidence: 96%
“…5 The eVect of exercise on platelet aggregability remains uncertain, with reports indicating an increase, [6][7][8][9][10][11][12] no change, [13][14][15][16] or even a decrease 17 in platelet reactivity. The eVect of exercise on platelet adhesion is also poorly defined, in part because of the use of methodology that could not reliably distinguish platelet adhesion from aggregation in those studies.…”
mentioning
confidence: 99%